2008
DOI: 10.1007/978-1-59745-033-1_4
|View full text |Cite
|
Sign up to set email alerts
|

In-Line Probing Analysis of Riboswitches

Abstract: Riboswitches are intricate, metabolite-binding RNA structures found in the non-coding regions of mRNA. Allosteric changes in the riboswitch that are induced by metabolite binding are harnessed to control the genes of a variety of essential metabolic pathways in eubacteria and in some eukaryotes. In this chapter, we describe an RNA structure analysis technique called "in-line probing." This assay makes use of the natural instability of RNA to elucidate secondary structure characteristics and ligand-binding capa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
324
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 303 publications
(344 citation statements)
references
References 10 publications
5
324
0
Order By: Relevance
“…We therefore introduced a mutation to this region and measured the binding affinity and cooperativity using in-line probing to obtain the apparent K d and Hill coefficient (n), respectively (Table 1; Regulski and Breaker 2008). NAIM experiments showed N-methyl G interference at G127, which suggested that the exocyclic amine of the nucleotide could be involved in minor groove hydrogenbonding interactions (Rife et al 1998;Kwon and Strobel 2008).…”
Section: Resultsmentioning
confidence: 99%
“…We therefore introduced a mutation to this region and measured the binding affinity and cooperativity using in-line probing to obtain the apparent K d and Hill coefficient (n), respectively (Table 1; Regulski and Breaker 2008). NAIM experiments showed N-methyl G interference at G127, which suggested that the exocyclic amine of the nucleotide could be involved in minor groove hydrogenbonding interactions (Rife et al 1998;Kwon and Strobel 2008).…”
Section: Resultsmentioning
confidence: 99%
“…Ribonucleases with different cleavage specificities are also used to identify single-or double-stranded regions, as well as protein-protected regions (RNase footprinting). Other methods such as selective 29-hydroxyl acylation analyzed by primer extension (SHAPE) (Wilkinson et al 2006) and in-line probing (Regulski and Breaker 2008) assess local nucleotide flexibility. SHAPE has since been adapted for high-throughput analysis (SHAPE-Seq) (Lucks et al 2011), joining other techniques that rely on RNase digestion such as fragmentation sequencing (FragSeq) (Underwood et al 2010) and parallel analysis of RNA structure (PARS) (Kertesz et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In vitro transcribed RNA was radiolabeled with γ-32 P ATP using T4 polynucleotide kinase (New England Biolabs) following standard procedures (38). After PAGE purification, RNAs were passed through an Illustra MicroSpin G-25 Column (GE Healthcare) and eluted with ddH 2 O. Inline probing assays (1× in-line buffer: 50 mM Tris·HCl, pH 8.3, 20 mM MgCl 2 , 100 mM KCl) were performed as previously described (37) for the extended Gs1761 riboswitch with terminator construct.…”
Section: Bioinformatic Analysis Of Gemm-i Variantsmentioning
confidence: 99%